Feasibility Study and Preliminary Results of Prognostic Value of Bone SPECT-CT Quantitative Indices for the Response Assessment of Bone Metastatic Prostate Carcinoma to Abiraterone - de Laroche, Romain; Bourhis, David; Robin, Philippe; Delcroix, Olivier; Querellou, Solène; Malhaire, Jean-Pierre; Schlurmann, Friederike; Bourbonne, Vincent; Salaün, Pierre-Yves; Schick, Ulrike; Abgral, Ronan (Frontiers in Medicine, 2020)
Objective We assessed the prognostic value of quantitative indices extracted from bone SPECT-CT to evaluate the response of bone metastatic castrate-resistant prostate cancer (BmCRPC) to abiraterone. Methods Consecutive patients with BmCRPC initiating treatment with abiraterone from March 2014 to March 2015 were prospectively included. Three 2-bed SPECT-CT (at baseline [M0], after 3 months [M3] and 6 months [M6] of treatment), were planned (Symbia Intevo®, Siemens). SPECT data were reconstructed using an Ordered Subset Conjugate Gradient Minimization (OSCGM) algorithm allowing SUV quantification. SUVmax and SUVpeak of the highest uptake lesion were measured in each SPECT-CT. Total Neoplastic Osteoblastic Metabolic Volume (NOMV) was assessed. PSA level was recorded at baseline, M3 and M6 of treatment. Overall survival (OS), progression-free survival (PFS) and disease-specific survival (DSS) were calculated. Results Nineteen patients aged 71.1±7.7 years were included. Low M0 SUVmax was significantly predictive of longer OS (p=0.04). Low NOMV at M0 were significantly predictive of longer PFS (p=0.02). Patients with increase of at least 12.5% of the SUVpeak of the highest uptake lesion between M0 and M3 (ΔSUVpeakM0M3) had a significantly longer OS (p=0.03). Patients with increase (or decrease lesser than 25%) of ΔSUVpeakM0M3 had a significantly longer DSS (p=0.01). Patients with increase of NOMV of at least 45% between M0 and M6 had a significantly shorter PFS (p<0.001). Variations of NOMV between M0 and M6 were significantly correlated with PSA variations between M0 and M6 (rs=0.73, p=0.02). Conclusions Quantitative bone SPECT-CT appears to be a promising tool of BmCRPC assessment. Early flare-up phenomenon seems to predict longer OS. Key-words: prostate cancer; bone scintigraphy; SPECT-CT; quantification; prognosis.